Identifying the main causes of amnesia using fuzzy analytic hierarchy process (AHP) / A’ina Najwa Masri - Masri, A’ina Najwa (2021)
Amnesia is a form of memory loss. Memory loss is the major symptom of amnesia, or unable to construct new, fresh or unique memories. People with amnesia may find it difficult to remember the facts, events, locations, or particular details. Some authors have different opinions about the causes of the amnesia. Hence, we need to conduct this study so that we can determine the main cause of the amnesia. The objective of this study is to identify the main causes of amnesia based on head injury, heat stroke, anoxia, and anaesthetics through the expertise guidelines using Fuzzy Analytical Hierarchy Process (AHP). While the triggers showed some fuzziness, it was possible to identify the Fuzzy AHP using linguistic variables and fuzzy numbers. Therefore, the Fuzzy Analytic Hierarchy Process (F-AHP) option is the best method for this reason. Based on the study's findings, the most common cause of amnesia with the highest normalized value of 37.9 percent is a head injury. In conclusion, the basis of the findings revealed that all the causes of amnesia have been captured and ranked by Fuzzy Analytic Hierarchy Process (F-AHP) with reasonable accuracy. Therefore, the analysis may be useful for future work in this area related to amnesia.